Toward stakeholders’ understanding of media reporting on doctor–patient relationship issues: trust, unfamiliarity and uncertainty in the Chinese context - Gao, Zhenghan; Huang, Junyang; Zhang, Bowen; Zhang, Xinwen (Frontiers in Public Health, 2024)
IntroductionThis study explores doctors’ and patients’ understandings of citizen journalism on doctor–patient relationship issues. It also examines the communication effect of citizen journalism as a communication platform on doctors and patients who are taking part in the doctor–patient relationship in contemporary China.MethodThis study draws on the analysis of 24 semi-structured interviews with doctors from both publicly funded and privately operated hospital, and nine focus groups which included 36 patients with different socio-economic backgrounds.ResultThe empirical research present the following results: (1) authority and witness are the two key factors to construct the stakeholders’(doctors’ and patients’) awareness and trust of citizen journalist reporting on the doctor–patient relationship issues. (2) stakeholders’ perception on citizen journalism will construct them concern on the uncertain and unfamiliar knowledge during the hospital activities.DiscussionThe interpretation of doctor–patient relationship reports by doctors and patients affects their mutual trust. Authority and witnessing are two key factors that citizen journalists should consider when reporting on doctor–patient relationship news. Doctors from different types of hospitals and patients with different income levels have different understandings of the authority and witnessing of the reported content. Reading the content of doctor–patient conflicts reflected in citizen journalist reports can exacerbate the emotional fluctuations of doctors and patients. After reading these reports, doctors and patients may experience increased anxiety about uncertainty and unfamiliarity in doctor–patient communication.ContributionThis study provides a framework for public health research from the relationship between communication content and audience. It also provides answers from the perspectives of media and stakeholders to investigate the tension in doctor–patient relationships in China.